Entretenimento, consumo e sociabilidade no K-Pop: construções e experiências sociais no fandom Army em Belém do Pará. - PEREIRA, Raíssa Abraçado (Universidade Federal do Pará, 2024)
This present research seeks to analyze, through entertainment as an experience and construction of the social, the consumption of South Korean pop and the practices of sociability in the Army fandom, which is the fandom of the main K-pop group today, BTS (Bangtan Sonyeodan). From a netnographic communication-Anthropological approach and with ethnographic inspirations, we joined the field with participant observation of the fandom Army, aiming to understand how the consumption practices of these fans impact and contribute to the development of sociabilities and interaction practices among the fan community and between fan and BTS group. The analyzes are based, mainly, on theoretical contributions about consumption, sociability, fan culture and material culture. The methodological procedures include the application of online questionnaires, in-depth interviews via Google Meet and field observations on social networks. It is considered, from the analysis of reports and field observations, the importance of fans for the K-pop entertainment industry, because we identify them as the main agents for the dynamics of the industry and consumption, as well as the sociability that in this sphere is necessary for the codes to be familiar in the most diverse contexts.